Assumptions of proceeding in juvenile cases in the court practice (Biuletyn Kryminologiczny, 2021)
Article is a summary of the research project realized in The Institute of Law Studies of the PolishAcademy of Sciences. In the course of project, there were conducted national surveys addressed to juvenile judges, professional family probation officers, experts from diagnostic teams and the individual in-depth interviews with selected representatives of these groups. The aim of the article is to present the results of the researches, the mainly the answer on the question how do juvenile courts realize in practice the assumptions of the Act on Proceeding in Juvenile Cases. Researches, in the application of law, have been considered particularly important because the law obliges the juvenile judges to collect information about juvenile and his/her environment – directly or indirectly (by supporting institutions).Artykuł stanowi podsumowanie projektu badawczego zrealizowanego w Instytucie Nauk Prawnych Polskiej Akademii Nauk. W ramach projektu zostały przeprowadzone dwa rodzaje badań: 1) ogólnopolskie badania sondażowe skierowane do trzech grup respondentów – sędziów dla nieletnich, zawodowych kuratorów rodzinnych oraz specjalistów zatrudnionych w opiniodawczych zespołach sądowych specjalistów, 2) indywidualne półustrukturyzowane wywiady jakościowe z przedstawicielami tych trzech grup zawodowych. W artykule zostały zamieszczone tylko niektóre wyniki. Szczególna uwaga została poświęcona realizacji założeń Ustawy o postępowaniu w sprawach nieletnich w praktyce orzeczniczej sądu. Potrzebę badań w tym zakresie uzasadnia fakt ustawowego zobowiązania sędziego dla nieletnich do gromadzenia informacji o nieletnim i jego środowisku - bezpośrednio lub pośrednio przy wykorzystaniu instytucji pomocniczych.